Report on VALIANT stakeholder survey - Nicolaou, Anna; Gutierrez, Begoña F. (My University, 2021)
This report presents the findings of a survey aiming at collecting insights from various stakeholders about the international virtual exchanges designed by the VALIANT research group. The survey was administered to primary and secondary education teachers, school managers, administrators, and university teacher trainers. The analysis of almost 2000 responses provided an understanding of the stakeholders’ interest in the VALIANT virtual exchange projects as well as their preferences and needs for the projects’ configurations and modalities. Key aspects presented in this report pertain to the respondents’ profiles and their experiences with working in rural or isolated areas. The information yielded from this survey was useful for VALIANT’s researchers who aspire to design beneficial virtual exchanges for in-service teachers, student teachers and educational experts.
Keywords: Virtual exchange; Stakeholders survey